Charge accumulation and dissipation characteristics of rGO / CNTs / EP composite coating - ZHAO Xin; XING Yilong; LI Meng; HUANG Chengchao; ZHAO Haodong; YANG Huarong (Journal of Aeronautical Materials, 2022)
The process of charge accumulation and dissipation on the surface of rGO / CNTs / EP composite coating was analyzed theoretically, and the fitting analysis was carried out according to the experimental data. The rationality of the theoretical model and the factors affecting the charge dissipation were discussed. On this basis, three kinds of charge dynamic change models were adopted to fit the measured data analysis, revealed the fitting curve and charge accumulation and dissipation process parameters such as time constant, fitting coefficient, and compared with the theoretical change curve, verified the charge and time constant, the relationship between the changes of the rationality of the evaluation model with a coating of charge dissipation effect. The results show that: compared with the accumulation model, the complex model better reflects the change process of charge accumulation process. With the increase of rGO / CNTs content in the coating, the ratio of accumulation time constant to dissipation time constant increases, the peak value of accumulated charge decreases and the dissipation effect increases. The dissipation model is basically consistent with the actual trend of charge dissipation process. With the increase of rGO / CNTs content, the dissipation time constant decreases and the dissipation effect increases.